Welcome letter from the editor - Montgomery, D. Philip (NUGSE Research in Education, 2(2), 2017)
The journal issue in front of you marks the fourth issue of NUGSE Research in Education. The authors, peer reviewers, and editors who have worked to keep this project growing and thriving understand too well the difficulty and messiness of writing—and yet they persist...
Keywords: welcome letter; NUGSE Research in Education